First-line immunotherapy of metastatic renal cell carcinoma: an updated network meta-analysis including triplet therapy - Yanagisawa, Takafumi; Kawada, Tatsushi; Bekku, Kensuke; Laukhtina, Ekaterina; Rajwa, Pawel; von Deimling, Markus; Chlosta, Marcin; Quhal, Fahad; Pradere, Benjamin; Karakiewicz, Pierre I; Mori, Keiichiro; Kimura, Takahiro; et al. (BJU international, 2024)
OBJECTIVE: To compare the differential efficacy of first-line immune checkpoint inhibitor (ICI)-based combined therapies among patients with intermediate- and poor-risk metastatic renal cell carcinoma (mRCC), as recently, the efficacy of triplet therapy comprising nivolumab plus ipilimumab plus cabozantinib has been published. PATIENTS AND METHODS: Three databases were searched in December 2022 for randomised controlled trials (RCTs) analysing oncological outcomes in patients with mRCC treated with first-line ICI-based combined therapies. We performed network meta-analysis (NMA) to compare the outcomes, including progression-free survival (PFS) and objective response rates (ORRs), in patients with intermediate- and poor-risk mRCC; we also assessed treatment-related adverse events. RESULTS: Overall, seven RCTs were included in the meta-analyses and NMAs. Treatment ranking analysis revealed that pembrolizumab + lenvatinib (99%) had the highest likelihood of improved PFS, followed by nivolumab + cabozantinib (79%), and nivolumab + ipilimumab + cabozantinib (77%). Notably, compared to nivolumab + cabozantinib, adding ipilimumab to nivolumab + cabozantinib did not improve PFS (hazard ratio 1.02, 95% confidence interval 0.72-1.43). Regarding ORRs, treatment ranking analysis also revealed that pembrolizumab + lenvatinib had the highest likelihood of providing better ORRs (99.7%). The likelihoods of improved PFS and ORRs of pembrolizumab + lenvatinib were true in both International Metastatic RCC Database Consortium (IMDC) risk groups. CONCLUSIONS: Our analyses confirmed the robust efficacy of pembrolizumab + lenvatinib as first-line treatment for patients with intermediate or poor IMDC risk mRCC. Triplet therapy did not result in superior efficacy. Considering both toxicity and the lack of mature overall survival data, triplet therapy should only be considered in selected patients.
Keywords: fenylmočovinové sloučeniny; Network Meta-Analysis as Topic; Quinolines; Nivolumab; randomizované kontrolované studie jako téma; humanizované monoklonální protilátky; Pyridines; Immunotherapy; Antineoplastic Combined Chemotherapy Protocols; Immune Checkpoint Inhibitors; nivolumab; doba přežití bez progrese choroby; Carcinoma, Renal Cell; Kidney Neoplasms; inhibitory kontrolních bodů; imunoterapie; síťová metaanalýza; ipilimumab; karcinom z renálních buněk; Phenylurea Compounds; anilidy; Anilides; Ipilimumab; chinoliny; pyridiny; nádory ledvin; protokoly protinádorové kombinované chemoterapie; lidé; Humans; Randomized Controlled Trials as Topic; Antibodies, Monoclonal, Humanized; Progression-Free Survival